2018
DOI: 10.1038/s41467-018-03902-9
|View full text |Cite
|
Sign up to set email alerts
|

Pausing controls branching between productive and non-productive pathways during initial transcription in bacteria

Abstract: Transcription in bacteria is controlled by multiple molecular mechanisms that precisely regulate gene expression. It has been recently shown that initial RNA synthesis by the bacterial RNA polymerase (RNAP) is interrupted by pauses; however, the pausing determinants and the relationship of pausing with productive and abortive RNA synthesis remain poorly understood. Using single-molecule FRET and biochemical analysis, here we show that the pause encountered by RNAP after the synthesis of a 6-nt RNA (ITC6) rende… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 67 publications
10
91
0
Order By: Relevance
“…We infer that initial-transcription pausing and transcription-elongation pausing share mechanistic commonalities. Consistent with this proposal, substitution of the RNAP b-subunit residue 446 (b D446A ), increases sequence-dependent pausing in both initial transcription ( Figure 3A; Dulin et al, 2018) and transcription elongation (Vvedenskaya et al, 2014). (Figures 4, S2), (iii) showed that initial-transcription pausing can occur at each promoter position in the promoter-initial-transcribed region from +3 to +9 (Figures 4, S2), (iv) and showed that the s finger contributes quantitatively to pausing at promoter positions +5 and +6, presumably through collision with the RNA 5ʹ end (Figures 3, 5E,F).…”
Section: Relationship Between Sequence Determinants For Initial-transsupporting
confidence: 71%
See 1 more Smart Citation
“…We infer that initial-transcription pausing and transcription-elongation pausing share mechanistic commonalities. Consistent with this proposal, substitution of the RNAP b-subunit residue 446 (b D446A ), increases sequence-dependent pausing in both initial transcription ( Figure 3A; Dulin et al, 2018) and transcription elongation (Vvedenskaya et al, 2014). (Figures 4, S2), (iii) showed that initial-transcription pausing can occur at each promoter position in the promoter-initial-transcribed region from +3 to +9 (Figures 4, S2), (iv) and showed that the s finger contributes quantitatively to pausing at promoter positions +5 and +6, presumably through collision with the RNA 5ʹ end (Figures 3, 5E,F).…”
Section: Relationship Between Sequence Determinants For Initial-transsupporting
confidence: 71%
“…Plots of RNAP occupancy as a function of initial-transcribed-region sequence shows graphically that RNAP occupancy strongly correlates with match to the consensus sequence for each position ( Figure S4). We note that placCONS, the promoter previously shown to exhibit initial-transcription pausing at a position in the range +5 to +7 in vitro (Duchi et al, 2016;Lerner et al, 2016;Dulin et al, 2018), and shown here to exhibit initial transcription pausing at position +6 in vitro and in vivo (Figure 3), contains a 3-of-3 match to the consensus sequence in the register that would yield initial transcription pausing at position +6 (compare Figure 3A and Figure 5A).…”
Section: Promoter-sequence Determinants For Initial-transcription Pausupporting
confidence: 52%
“…The high FRET state presumably represents the scrunched DNA template at position +2, and our results suggest that the scrunched TIC can become unscrunched, switching to a conformation similar to that of the open promoter state, and can sometimes even switch back to the closed promoter state, presumably following the dissociation of RNA product by abortive initiation. Such scrunching-unscrunching dynamics during transcription initiation were recently observed in bacterial transcription machinery and were suggested to provide a paused checkpoint for abortive and productive RNA synthesis 3 . Upon stalling the TIC at positions +3, +5, +6, and +7, the major FRET population progressively rose to higher FRET levels of 0.63, 0.66, 0.76, and 0.79, respectively.…”
Section: Resultsmentioning
confidence: 67%
“…Recent studies of transcription machinery have found that transcription initiation is not a unidirectional process that invariably leads to elongation, but is rather a stochastic process that involves divergent pathways such as abortive initiation, backtracking, and pausing in addition to the progression to elongation 1-6 . These findings suggest that clearing initiation and progressing to elongation might be rate-determining steps that control transcription efficiency, and they have been suggested to be targets of transcription regulation 3,7-9 . Transcription systems across lineages with different levels of complexity show highly variable initiation efficiencies that depend on specific DNA elements 10,11 .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation